Locating Mandibular Foramen in Children with Mandibular Retrognathism in Mixed Dentition - Mehrsa Paryab; Maryam Ahmadyar (Tabriz University of Medical Sciences, 2015)
Background and aims. One of the most common reasons forthe inferior alveolar nerve block anesthesia failure is the variation in mandibular foramen location. The aim of this study was to assess the location of mandibular foramen in chil-dren with mandibular retrognathism in comparison to children with normal skeletal occlusion in the mixed dentition. Materials and methods. One hundred and twenty panoramic radiographs of patients in mixed dentition period, undergo-ing orthodontic treatment, were selected based on inclusion criteria, skeletal occlusion and stage of dental development. The radiographs were divided into two groups: I: 60 panoramic radiographs of patients with normal skeletal occlusion (15 in each of the Hellman dental age stages); II: 60 panoramic radiographs of patients with mandibular retrognathism (15 in each of the Hellman dental age stages). The radiographs were traced and the linear distance from the mandibular foramen to the borders of the mandibular ramus and its angular position were identified. The measurements were compared between the two groups and among the four dental age groups by t-test, ANOVA and post hoc tests. Results. No statistically significant differences werefound between the patients with normal skeletal occlusion and patients with mandibular retrognathism (P>0.05). Statistical tests showed significant differences in the vertical location of mandibu-lar foramen and gonial angle between the four dental age groups (P<0.05). Conclusion. Mandibular retrognathism does not have a significant impact on the location of the mandibular foramen in the mixed dentition period. The child's dental age would be considered in the localization of the mandibular foramen.